Factors Affecting Income Seaweed Farmers in Tompotana Village Tanakeke Islands District Takalar Regency - Mirwan, Mirwan; Akhmad, Akhmad; Jam’an, Andi (Journal Social Society, 2025)
Seaweed is one of the leading commodities that plays a vital role in improving the coastal community's economy and supporting sustainable development goals (SDGs). However, the income of seaweed farmers in Tompotana Village, Tanakeke Islands District, Takalar Regency remains unstable and is influenced by various factors that have not been thoroughly identified through scientific research. This study aims to analyze the factors that affect the income of seaweed farmers, particularly focusing on capital, production, and selling price. A quantitative research approach was applied using a survey method. The sample was purposively selected from seaweed farmers residing in Tompotana Village. Data collection techniques included structured interviews, questionnaires, and documentation. The study utilized primary data, which was analyzed using the Statistical Package for the Social Sciences (SPSS) version 24, employing multiple linear regression analysis. The results show that: (1) capital does not have a significant effect on seaweed farmers’ income, either partially or simultaneously; (2) production has a significant effect on income; and (3) selling price also has a significant effect on income. These findings indicate that income improvement is more strongly influenced by production levels and market price dynamics rather than the amount of capital invested. Therefore, strategies to enhance seaweed farmers’ income should focus on increasing productivity and improving market access rather than merely increasing capital input. This study is expected to serve as a foundation for policymakers in designing more effective and sustainable coastal community economic empowerment programs.